Acute effects of verbal feedback on explosive upper-body performance in elite athletes - Argus, C.; Gill, N.; Keogh, J.; Hopkins, W. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to determine the effects of verbal feedback on the explosive upper-body performance of well-trained rugby union athletes in a resistance training session. Athletes (n = 9) completed two sessions of bench-throws with peak velocity feedback after each repetition, and two identical sessions without feedback. Within each session, three sets of four repetitions of bench-throw were completed. When feedback was received there was a small increase of 1.8% (90% confidence limits, ±2.7%) and 1.3% (±0.7%) in average peak power and velocity when averaged over the three sets. When individual sets were compared, there was a tendency towards greater increases in average peak power in the second and third sets. Benefits of feedback may be greatest in the latter sets of training and could improve training quality and adaptation.